Group Empowerment Trough Kawasan Rumah Pangan Lestari (KRPL) in Karangbesuki Village, Malang City - Hanafi Ihya; Yana Syafrieyana; Iradhad Taqwa Sihidi (Universitas Muhammadiyah Malang, 2020)
This study aims to determine the empowerment process in the KRPL program conducted by the Malang Agriculture Service-KP Office at Cemara Hijau KWT Karangbesuki Village. This program is the government's effort to maintain the existence of agriculture and food security from decreasing urban agricultural land through the empowerment of domestic women's groups. This type of research is descriptive qualitative, using Wilson's empowerment process which includes the process of awakening, understanding, harnessing, and using. Data collection techniques are observation, interviews, and documentation. The results of the empowerment research on the vegetable cultivation activity KRPL program, KWT CHF can produce food contributions with a harvest weight of 25-40 kg. Within one month KWT CHF earns an income of around Rp. 1,000,000 to Rp. 2,500,000 from the sale of harvested vegetables. The income is used to pay salaries of Rp. 5,000 per day to active CHF KWT members. Active members earn income around Rp. 250,000 to Rp. 350,000 per month. The research concludes that KWT CHF has been empowered and can be said to be successful. This success was seen from the additional income obtained by KWT CHF from the KRPL program activities in Karangbesuki Village.Keywords: Empowering Women Farmers Group, revenue additions, KRPL Program